2008
DOI: 10.1029/2007ja012829
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the multiple‐component structure of the 20 January 2005 cosmic ray ground level enhancement

Abstract: [1] Worldwide observations of the cosmic ray ground level enhancement (GLE) of 20 January 2005 are used to investigate a commonly observed but poorly understood feature of this class of event. It is argued that the GLE comprised two distinctly different cosmic ray populations. The first resulted in an impulsive, highly anisotropic, field-aligned pulse with a relatively hard rigidity spectrum and significant velocity dispersion. The characteristics of the anisotropy were almost identical to those for similar im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…Results for the relativistic SEP event of 2005 Jan. 20 presented in Paper I and the present work are consistent with the basic scheme of successive relativistic particle releases during a GLE devised by Miroshnichenko (2001, and references therein), Vashenyuk et al (2006), and McCracken et al (2008. Our observations relate the acceleration processes to evolving large-scale magnetic structures in the corona and therefore to the CME development.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Results for the relativistic SEP event of 2005 Jan. 20 presented in Paper I and the present work are consistent with the basic scheme of successive relativistic particle releases during a GLE devised by Miroshnichenko (2001, and references therein), Vashenyuk et al (2006), and McCracken et al (2008. Our observations relate the acceleration processes to evolving large-scale magnetic structures in the corona and therefore to the CME development.…”
Section: Resultssupporting
confidence: 90%
“…It displayed a well-defined, rapidly rising time profile at the beginning and a distinct second peak a few minutes later. Evidence that the first release was related to particle acceleration in the flaring active region in the low corona was brought by different publications (e.g., Simnett 2006Simnett , 2007Kuznetsov et al 2008;Grechnev et al 2008;McCracken et al 2008;Masson et al 2009). In the present paper we complete the investigation of Masson et al (2009, hereafter Paper I) through a detailed comparison between the second peak of the relativistic proton time profile derived from neutron monitor measurements with high-quality radio and UV observations.…”
Section: Introductionmentioning
confidence: 99%
“…Whether a given SEP event is a GLE depends on the detection of the secondary particles usually by neutron monitors (NMs) at cosmic ray stations. For a given GLE, different NMs show different time profiles (e.g., Bieber et al 2002;McCracken et al 2008;Moraal and McCracken 2011), because of different asymptotic look angles and rigidities of the NMs combined with anisotropy of the particles.…”
Section: Problems In Defining and Characterizing Glesmentioning
confidence: 99%
“…Another view, however, is that some GLEs come directly from solar flares, which may also accelerate particles to high energies in magnetic reconnection, primarily because their temporal variations mimic those of impulsive flares (Grechnev et al 2008;McCracken et al 2008). Aschwanden (2012) also argued that, in five of the 13 GLEs he studied, the particles are released during the impulsive phase of the associated flare.…”
Section: Introductionmentioning
confidence: 99%
“…Another distinguishing factor is the particle composition: impulsive events are characterized as electron-and 3 He-rich and with enhanced abundances of heavy ions (e.g., Reames et al, 1985;Reames, 1988), whereas the particle composition of gradual events more or less resembles that of the solar corona (e. g., Meyer, 1985). Although GLEs are usually considered as extreme examples of gradual events, some studies suggest that GLEs have a direct flare component, based on their temporal behaviour (Grechnev et al, 2008;McCracken et al, 2008), or particle composition and charge states (Cohen et al, 1999;Mason et al, 1999;Möbius et al, 1999). It has also been suggested that the energy-dependent composition and charge states in these events can be understood in terms of evolving shock-normal angle in a shock acting on remnant flare suprathermals from earlier flare activity (Tylka et al, 2005;Tylka and Lee, 2006;Sandroos and Vainio, 2007;Sandroos and Vainio, 2009).…”
Section: Introductionmentioning
confidence: 99%